1995
DOI: 10.1901/jaba.1995.28-97
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Interspersed Requests and Social Comments as Antecedents for Increasing Student Compliance

Abstract: Two students were alternately presented with interspersed high-compliance requests and social comments as antecedents to low-compliance requests. An initial comparison demonstrated similar positive effects on compliance for interspersed requests and social comments. A second analysis indicated that the effectiveness of social comments for increasing compliance was related to the time interval between social comments and low-compliance requests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 3 publications
3
38
0
Order By: Relevance
“…High-p instruction sequences involve the rapid presentation of three instructions with which an individual is likely to comply immediately preceding an instruction with a low probability of compliance. This procedure has been used successfully to increase compliance and decrease aberrant behavior in adults with developmental disabilities (e.g., Mace & Belfiore, 1990;Zarcone, Iwata, Mazaleski, & Smith, 1994) as well as children and youth with severe handicaps (e.g., Davis, Brady, Hamilton, McEvoy, & Williams, 1994;Ducharme & Worling, 1994;Horner, Day, Sprague, O'Brien, & Heathfield, 1991;Houlihan, Jacobson, & Brandon, 1994;Kennedy, Itkonen, & Lindquist, 1995;Singer et al, 1987).…”
mentioning
confidence: 99%
“…High-p instruction sequences involve the rapid presentation of three instructions with which an individual is likely to comply immediately preceding an instruction with a low probability of compliance. This procedure has been used successfully to increase compliance and decrease aberrant behavior in adults with developmental disabilities (e.g., Mace & Belfiore, 1990;Zarcone, Iwata, Mazaleski, & Smith, 1994) as well as children and youth with severe handicaps (e.g., Davis, Brady, Hamilton, McEvoy, & Williams, 1994;Ducharme & Worling, 1994;Horner, Day, Sprague, O'Brien, & Heathfield, 1991;Houlihan, Jacobson, & Brandon, 1994;Kennedy, Itkonen, & Lindquist, 1995;Singer et al, 1987).…”
mentioning
confidence: 99%
“…However, investigators have identified a number of dimensions that are salient in one or more cases, including task difficulty (Carr & Durand, 1985a;Weeks & Gaylord-Ross, 1981), type of required motor responses (Dunlap, KernDunlap, Clarke, & Robbins, 1991), number of required responses (Mace, Browder, & Lin, 1987), task novelty (Mace et al, 1987), duration of instructional sessions (Dunlap et al, 1991), rate of task presentation (Smith, Iwata, Goh, & Shore, 1995), unpredictability of events (Flannery & Horner, 1994), and task preference (Dunlap et al, 1991;Foster-Johnson, Ferro, & Dunlap, 1994). In addition, the probability of problem behavior following a particular demand may be reduced by prior or interspersed events such as storytelling (Carr, Newsom, & Binkoff, 1976), social comments (Kennedy, Itkonen, & Lindquist, 1995), demands highly likely to be complied with (Mace & Belfiore, 1990), and advance notification (Tustin, 1995). Much of the literature on social-negative reinforcement has focused on escape from demands.…”
Section: Social-negative Reinforcementmentioning
confidence: 99%
“…In treating a developmentally disabled adult, Mace et al demonstrated that by issuing a sequence of three to five commands the subject was likely to comply with (high-p commands) prior to issuing a command s/he was unlikely to comply with (low-p commands), compliance to the low-p commands could be dramatically increased. This strategy has been successfully replicated across a variety of populations including autistic children (Davis, Brady, Williams, & Hamilton, 1992;Houlihan, Jacobson, & Brandon, 1994), individuals with selfinjurious behaviors (Horner, Day, Sprague, O'Brien, & Heathfield, 1991;Zarcone, Iwata, Mazaleski, & Smith, 1994), children with social skills deficits (Davis, Brady, Hamilton, McEvoy, & Williams, 1994;Kennedy, Itkonen, & Lindquist, 1995), and individuals who are being noncompliant with specific medical regimens (Harchik & Putzier, 1990).…”
Section: Out Of the Operant Chamber And Into The Classroommentioning
confidence: 99%
“…A recent example is provided by Kennedy, Itkonen, and Lindquist (1995). In their treatment of two students with severe disabilities, Kennedy et al (1995) alternately presented interspersed high-p requests and social comments as antecedents to low-p requests.…”
Section: Proposing An Alternative Analysismentioning
confidence: 99%
See 1 more Smart Citation